FUNGI ASSOCIATED TO PLATYPUS CYLINDRUS FAB . ( COLEOPTERA : PLATYPODIDAE ) IN CORK OAK - Henriques, Joana; INÁCIO, MARIA D E LURDES; Sousa, Edmundo (Revista de Ciências Agrarias, 1996)
Platypus cylindrus is a pest that since the 80s of the last century has been considered a cork oak mortality agent in Portugal. It is an ambrosia beetle that establishes complex symbioses with fungi whose role in the insect-fungus-host interaction has not been completely clarified. In order to characterize P. cylindrus associated micoflora in Portugal, fungi were isolated from different beetle organs and from its galleries in cork oak trees. Fungi of the genera Acremonium, Aspergillus, Beauveria, Botrytis, Chaetomium, Fusarium, Geotrichum, Gliocladium, Nodulisporium, Paecilomyces, Penicillium, Raffaelea, Scytalidium, Trichoderma and of the order Mucorales were identified. An actinomycete of the genus Streptomyces was also identified. Some of these genera were related for the first time to this interaction. In the present work the isolated fungi are characterized and their contribution for beetle population establishment and tree weakness is discussed.
Keywords: Ambrosia beetle; decline; interaction; mycoflora; Quercus suber